Comprehensive exergy transfer analysis of a cyclonic furnace integrated recirculating mixed flow grain dryer. (5th January 2022) - Mondal, Md. Hasan Tarek; Akhtaruzzaman, Md.; Islsm, Md. Azadul; Sarker, Md. Sazzat Hossain
Highlights: A rice husk fired cyclonic furnace (CF) (capacity 0.5 MW) was designed and developed. Comprehensive exergy transfer for CF assisted MFD was analyzed during maize drying. Estimated thermal efficiency of the CF was 68.96 to 87.01% under full operation. Exergy efficiency of the dryer varied from 3.03 to 21.9% for high moisture grain. Exergy loss through direct heat exchanger was contrasted between 44.01 and 51.54 kJ/s. Abstract: Investigation of exergy transfer is an important aspect for all grain drying industry. Exergy transfer of rice husk fired cyclonic furnace assisted recirculating mixed flow dryer (MFD) equipped with a heat exchanger, was sought in this study. A cyclonic furnace (CF) having capacity 0.5 MW and recirculating MFD were designed and developed to investigate exergy transfer during grain drying. Efficiency of furnace was determined to quantify performance of CF for industrial grain drying system. Exergetic efficiency was also thoroughfare performed for the developed CF, air mixing chamber (heat exchanger) and MFD. Thermal efficiency of the CF varied from 68.96 to 87.01% during drying of high moisture maize grain. Exergy efficiency of the CF, heat exchanger and drying chamber marked between 58.8 and 63.5%, 74.6–93.29%, and 3.03–21.9%, respectively. Exploration of exergy inflow persist between 53.32 and 60.51 kJ/s and 7.58 to 9.81 kJ/s while exergy outflow ranged between 7.58 and 9.81 kJ/s and 1.52 to 3.10 kJ/s, respectively for heat exchanger and drying chamber. Results based on exergy losses indicates that 44.01–51.54 kJ/s and 5.87–7.50 kJ/s of exergy is just loss through heat exchanger and drying chamber, respectively. Exergy improvement potential and sustainability index varied between 1.02 and 1.80 kJ/s and 1.17–1.40 kJ/s, respectively. Quality of final product is in acceptable range as color difference of dehydrated maize kernel varied from 9.19 ± 0.46 to 17.05 ± 0.13. Exergy results indicate that CF can aptly be applied for grain drying industry in commercial scale.